2013
DOI: 10.1002/jctb.4015
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging microbial activity in cementitious systems: an emerging frontier in contaminated soil treatment

Abstract: Bioremediation is widely accepted as the most effective remediation technology for organic contamination. Nevertheless, it is ineffective for heavy metals, which cannot be degraded, and their immobilisation through pH control achieved with high‐pH cementitious materials is one of very few feasible means of treatment available. However, progress is being made in encouraging microbial activity in cementitious systems, which could provide a single technology that is effective and can be used for simultaneous trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…As a result, there are concerns regarding the long-term effectiveness of S/S treatment due to uncertainties in a number of areas like test methods, observed deficiencies in the process application, observed lack of chemical binding in crushed samples of treated wastes, and uncertainties of performance arising from anticipated behavioural degradation of the material over time (Perera et al 2005a). Consequently, recent studies have also considered combining S/S and biodegradation in order to achieve some form of (organic) contaminant attenuation over time (Kogbara 2013).…”
Section: Cemi S/s Treated Contaminated Soilsmentioning
confidence: 99%
“…As a result, there are concerns regarding the long-term effectiveness of S/S treatment due to uncertainties in a number of areas like test methods, observed deficiencies in the process application, observed lack of chemical binding in crushed samples of treated wastes, and uncertainties of performance arising from anticipated behavioural degradation of the material over time (Perera et al 2005a). Consequently, recent studies have also considered combining S/S and biodegradation in order to achieve some form of (organic) contaminant attenuation over time (Kogbara 2013).…”
Section: Cemi S/s Treated Contaminated Soilsmentioning
confidence: 99%
“…Besides, numerous abiotic factors including irreversible sorption of contaminants to the cementitious matrix, volatilization, and reductive dichlorination of chlorinated organic in the presence of Fe (II) [32] were implicated in the contaminant losses in previous studies treating artificially contaminated soils with two organic contaminants such as 2chlorobenzoic acid and phenol [31]. Nonetheless, the previous study [30] only used bacteria as the degrading agents in the S/S matrices.…”
Section: Activated Sludge (As) Pseudomonasmentioning
confidence: 99%
“…(Perera et al, 2005) identified various mechanisms that could impair the long-term efficiency of S/S. CO2 uptake leads to carbonation, reducing the initial alkalinity of specific materials (Kogbara, 2013;Kogbara et al, 2012). The possible health and environmental effects of contaminants generated in the petroleum industries, mainly drill cuttings, have accelerated awareness and criticism among communities.…”
Section: Introductionmentioning
confidence: 99%